Correction: Efficient and selective catalytic hydrogenation of furanic aldehydes using well defined Ru and Ir pincer complexes. Issue 1 (17th December 2020) - Padilla, Rosa; Koranchalil, Sakhitha; Nielsen, Martin
Abstract : Correction for 'Efficient and selective catalytic hydrogenation of furanic aldehydes using well defined Ru and Ir pincer complexes' by Rosa Padilla et al., Green Chem., 2020, 22, 6767–6772, DOI: ; 10.1039/D0GC01543A .